1993
DOI: 10.1093/jnci/85.22.1819
|View full text |Cite
|
Sign up to set email alerts
|

Migration Patterns and Breast Cancer Risk in Asian-American Women

Abstract: Because heterogeneity in breast cancer risk in these ethnic populations is similar to that in international comparisons and because analytic epidemiologic studies offer the opportunity to disentangle correlated exposures, this study should provide new insights into the etiology of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
556
2
23

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 961 publications
(607 citation statements)
references
References 17 publications
26
556
2
23
Order By: Relevance
“…Breast cancer incidence rates in South Asian women living in England are lower than those in the English native population, but higher than those in the Indian subcontinent (Harding and Rosato, 1999;Winter et al, 1999;Smith et al, 2003), consistent with studies in migrants from low-to high-risk countries in which incidence approaches that of the native population within one or two generations (Shimizu et al, 1991;Ziegler et al, 1993). Although rates are lower than that of the native population, breast cancer remains the most common cancer among South Asian women (Harding and Rosato, 1999;Winter et al, 1999).…”
supporting
confidence: 55%
“…Breast cancer incidence rates in South Asian women living in England are lower than those in the English native population, but higher than those in the Indian subcontinent (Harding and Rosato, 1999;Winter et al, 1999;Smith et al, 2003), consistent with studies in migrants from low-to high-risk countries in which incidence approaches that of the native population within one or two generations (Shimizu et al, 1991;Ziegler et al, 1993). Although rates are lower than that of the native population, breast cancer remains the most common cancer among South Asian women (Harding and Rosato, 1999;Winter et al, 1999).…”
supporting
confidence: 55%
“…Breast cancer incidence in native-born and USA-born AsianAmericans is approximately 50% and 75%, respectively, that of USA-born Whites and is approximately twice that of women residing in Asia (Ziegler et al, 1993;Hanley et al, 1995). Exposure to Western lifestyles is thought to have a substantial impact on the increased risk for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most Western countries have a high incidence, while the Netherlands is among the highest in the world (Van der Sanden et al, 1995). Differences in breast cancer incidence have been observed in the United States among different ethnic groups (Ziegler et al, 1993;Brinton et al, 1997). Studies of Japanese migrants to Hawaii have shown that breast cancer incidence adjusts to the incidence in the new homeland within one or two generations pointing to life style and environmental factors in aetiology (McPherson et al, 2000).…”
mentioning
confidence: 99%